A Gender-based Rasch Analysis of University Students’ Academic Stress - Shafna Utami Nur Fairuz; Dony Darma Sagita; Syifa Aisyah (PSIKOPEDAGOGIA Jurnal Bimbingan dan Konseling, 2022)
Stress has become one of the issues that draw considerable attention. While it does not cause health problems, it may affect individuals’ physical and psychological health.   This study attempted to see university students’ academic stress level differences in terms of gender. This descriptive comparative study involved 466 university students (346 female students, 120 male students) recruited as respondents using convenience sampling. An academic stress scale comprising three indicators, i.e., physical, emotional, and behavioral responses, was used to collect data. The data were analyzed using t-test, combined with RASCH stacking model. The result indicated that university students’ academic stress did not significantly differ in gender. This result could be used as a reference for developing a guidance and counseling service to handle university students’ academic stress, which could be preventive, development, and curative.